A Peaceful Rise: How China Sees its Global Role in 2024 - Reza Hasmath (The Journal of Intelligence, Conflict and Warfare)
On March 21st, 2024, Dr. Reza Hasmath presented A Peaceful Rise: How China Sees its Global Role in 2024 for the CASIS March 2024 Digital Roundtable. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the views of the Chinese population regarding international actors, their positioning in relation to Chinese international cooperation, their understanding of these relationships with Canada, and how Canada can play an important role in binding China to the West.